Effects of forage type on the rumen microbiota, growth performance, carcass traits, and meat quality in fattening goats - Wu, Zhou-lin; Yang, Xue; Zhang, Jiamin; Wang, Wei; Liu, Dayu; Hou, Bo; Bai, Ting; Zhang, Rui; Zhang, Yin; Liu, Hanyang; Hu, Hongwen; Xia, Yunhong (Frontiers in Veterinary Science, 2023)
Forages fed to goats influence ruminal microbiota, and further contribute to affect growth performance, meat quality and its nutritional composition. Our objective for current study was to investigate the effects of different forages on growth performance, carcass traits, meat nutritional composition, rumen microflora, and the relationships between key bacteria and amino acids and fatty acids in the longissimus dorsi and semimembranosus muscles of goats. Boer crossbred goats were separately fed commercial concentrate diet supplemented with Hemarthria altissima (HA), Pennisetum sinese (PS), or forage maize (FG), and then slaughtered 90 days after the beginning of the experiment. Growth performances did not vary but carcass traits of dressing percentage, semi-eviscerated slaughter percentage, and eviscerated slaughter percentage displayed significant difference with the treatment studied. Meats from goats fed forage maize, especially semimembranosus muscles are rich in essential amino acids, as well as an increase in the amount of beneficial fatty acids. Our 16S rRNA gene sequencing results showed that the Firmicutes, Bacteroidetes, and Proteobacteria were the most dominant phyla in all groups but different in relative abundance. Further, the taxonomic analysis and linear discriminant analysis effect size (LEfSe) identified the specific taxa that were differentially represented among three forage treatments. The spearman’s correlation analysis showed that rumen microbiota was significantly associated with the goat meat nutritional composition, and more significant positive correlations were identified in semimembranosus muscles when compared with longissimus dorsi muscles. More specifically, the lipid metabolism-related bacteria Rikenellaceae_RC9_gut_group showed positively correlated with meat amino acid profile, while genera Oscillospiraceae_UCG-005 were positively correlated with fatty acid composition. These bacteria genera might have the potential to improve nutritional value and meat quality. Collectively, our results showed that different forages alter the carcass traits, meat nutritional composition, and rumen microflora in fattening goats, and forage maize induced an improvement in its nutritional value.